Education on providing additional food for toddlers - Jusmawati, Jusmawati; Hasrida (Journal of Evidence-Based Community Health, 2024)
Toddlers are children who are vulnerable to infection, because their immune system is not yet optimal and strong. Toddlers' immune systems must be well maintained to support their growth and development processes. The role of parents is very important in providing balanced nutrition, such as providing additional food (PMT) for children as a way to improve their immune system. Providing supplementary food (PMT) to children under five is carried out as a supplementation strategy in overcoming nutritional problems so that malnutrition cases can be reduced. Nutritional problems in children under five can affect children's cognitive abilities and intelligence, and also cause low child productivity. Supplementary feeding (PMT) is an intervention program for toddlers suffering from malnutrition which aims to improve the nutritional status of children and to overcome nutritional deficiencies that occur in the toddler age group